Protagonismo Guarani-Kaiowá no ciberespaço: em busca da auto-representação - Neves, Erica Morais Ribeiro (2015)
After the popularization of Internet any connected citizen can disseminate news and introduce new topics of debate in the public sphere. We use here the concept of public sphere described by Habermas (1984) as the space that allowed the emergence of public debate, consolidator of modern democracy. Given this context, the research aims to reflect on the possibilities of connected citizens to take ownership of the new medias and take for themselves the place of enunciation, understood as part of a process of construction of their own citizenship. To conduct such a reflection, at first we tell the story of the people Guarani-Kaiowá. Then, we analyze the evolution of the concept of citizenship to emphasize the pressing need to consolidate these rights for marginalized people, as is the case of Brazilian Indians. We also make considerations about the conceptions of the Information Age through the development of orality to writing until the emergence of cyberspace. Finally, we try to understand what motivates citizens historically marginalized by traditional media to engage in the fight for the right to represent themselves in the cyberspace. The first answers we achieve show that in addition to the search for self-representation, the people Guarani-Kaiowá use the cyberspace as a strategic quest for visibility as their search for assistance and demarcation of land requires communications intermediation. This perception culminates in the conclusion that the use of cyberspace can be considered as an exercise of the citizenship by the people Guarani-Kaiowá.